Fast calcite growth driven by galvanic couples - Ifland, Cade Michael (Kansas State University, 2024)
The mineralization of carbon dioxide into calcite, and other carbonates, is a natural mechanism for carbon sequestration that has stimulated vigorous efforts to engineer carbon-capture solutions. It is known that one can deposit calcite by shifting the pH during electroprecipitation, where an overpotential is applied between the substrate and a counter electrode. This process can occur even without the use of electrochemical instrumentation. The presence of dissimilar metals in a mineral-rich soil causes a galvanic couple to become established when the soil gets wet, thus electro-precipitating carbonaceous salts from the soil-based solution. That said, the viability of electro-precipitation (EP) as a soil-based carbon capture strategy is unexplored. The goal of this research is more general; to measure calcite growth rates under a variety of different growth conditions. This growth can be driven by electroprecipitation, or be undriven growth in supersaturated solutions. To this end, we employ a purpose-built quartz crystal microbalance (QCM) coupled to a long working distance optical microscope; this permits the rapid nucleation of a known mass and number of calcite seeds on QCM plates. By transferring these seeded plates to the solutions we want to investigate, we can normalize the resulting growth rate by the active area of the crystal surface. We found that this normalization procedure works well, and that our growth rates in supersaturation are consistent with prior research. In addition, applied voltages can greatly increase growth rates, and are very effectively generated through galvanic coupling. Finally, we have found that a galvanic couple can be used to electroprecipitate carbonate minerals from water-saturated mineral-rich soil samples.
Keywords: Calcite; Quartz crystal microbalance (QCM); Growth rate; Crystal; Sequestration